Hospitalization of children with Down Syndrome - Ariel eTenenbaum; Rana N. Hanna; Diana eAverbuch; Isaiah D. Wexler; Maor eChavkin; Joav eMerrick; Joav eMerrick; Joav eMerrick (Frontiers Media S.A., 2014)
Children with Down syndrome present with multiple medical problems in a higher prevalence compared with the general population, which may lead to hospitalizations. Methods: Analysis of 560 hospitalizations of 162 children aged 0-16 years with Down syndrome at Hadassah Medical Center during the years 1988-2007 compared with data on children in the general population, hospitalized at the same period. Data was collected from patient files and statistical data from the Ministry of Health. Results: Respiratory infections were the leading cause for hospitalization of children with Down syndrome. The number of hospitalizations of children with Down syndrome compared to the number of all children, who were hospitalized was surprisingly similar to their proportion in the general population. Eleven children died during their hospitalization (five heart failure, three sepsis, one respiratory tract infection and one due to complication after surgery). Nine of the eleven had a congenital heart anomaly. Conclusions: Children with Down syndrome can present with complex medical issues and we support the concept of a multidisciplinary team that has experience and knowledge to serve as a one stop shop for these individuals and their families, with timely visits in which a comprehensive evaluation is performed, problems attended to and prevention plans applied. In this way we may prevent morbidity, hospitalizations and mortality.